Pengaruh Kontrol Diri dan Penggunaan Media Sosial Terhadap Prestasi Belajar Siswa - Nurwanti, Siti; Afriza, Edi Fitriana; Nurdianti, Raden Roro Suci (Educatio, 2024)
Student learning achievement in economics subjects is still less than the Minimum Completeness Criteria (KKM), namely 76, which is the main research problem. The aim of the research is to find out how the use of social media and self-control influence student learning outcomes in economics classes. The explanatory design survey method is the research methodology used. There are 233 students in class XI IPS at SMAN 1 Cikatomas for the 2023–2024 academic year. Using the Slovin formula and proportional sampling, the sample method produced 146 responses. In the data collection process, a closed questionnaire was used and several data analysis techniques were used, including the F test, R2 coefficient of determination test, heteroscedasticity test, multicollinearity test, normality test, and multiple linear regression analysis. The research results show that: 1) Self-control has a significant effect on learning achievement, with a significance value of (0.000 < 0.05). 2) The use of social media has a significant influence on academic achievement, with a significance value of (0.000 < 0.05). 3) Self-control and use of social media have a big influence on academic achievement, with a significance value (0.000 < 0.05). Research findings show that social media use and self-control have a major impact on students' academic success.